Study of Mobile Operator Readiness Measurement in Indonesia for 5G Technology Deployment - Sri Ariyanti; Alim Setiawan Slamet; Jono M Munandar (Centre for Research and Development on Resources, Equipment, and Operations of Posts and I, 2021)
The readiness of mobile operators in implementing 5G technology is essential in providing an overview for the government regarding the level of readiness of mobile operators so that they can provide input for policies that the government will issue regarding the deployment of 5G technology in Indonesia. This study aims to measure the level of readiness of mobile operators in 5G technology deployment. The research method by measuring the readiness index of mobile operators includes infrastructure, spectrum, demand, revenue, and ARPU. Research data is secondary data obtained from the Ministry of Communication and Information Technology. The results showed that PT. Telkomsel is the readiest to deploy 5G in Indonesia. For the next rank, namely PT. XL-Axiata, PT. Indosat, PT. Smartfren, H3I, and the last one is PT. Sampoerna Telekomunikasi Indonesia (STI).